Moral Education in Wasiat Renungan Masa by TGKH. Muhammad Zainuddin Abdul Madjid: An Examination of Ibn Miskawaih's Philosophy - Atsani, Lalu Gede Muhammad Zainuddin; Nasri, Ulyan; Walad, Muzakkir; Yakin, Hakkul; Zulkifli, Muh. (Jurnal Ilmiah Profesi Pendidikan, 2023)
This research discusses the moral education found in “Wasiat Renungan Masa” by TGKH. Muhammad Zainuddin Abdul Madjid through an examination of Ibn Miskawaih's moral philosophy. The aim of this study is focused on understanding moral education within “Wasiat Renungan Masa” by using the lens of Ibn Miskawaih's moral philosophy. The research method employed is a literature analysis, which includes the identification of research objectives, data identification, data collection, data selection, data extraction, thematic analysis, comparison, contrast, pattern identification, as well as research conclusions and implications. The results of this study indicate that moral education in "Wasiat Renungan Masa" by TGKH. Muhammad Zainuddin Abdul Madjid, as examined through the philosophy of Ibn Miskawaih, emphasizes the importance of self-development and morality in living life. Through concepts of self-discipline, moral exercises, and the cultivation of good character, humans have the potential to attain spiritual happiness and moral perfection. The conclusion of this research provides a deeper insight into the moral values within these works and their relevance in the context of contemporary moral education. This research has practical implications in the development of moral education, the formation of individual character, and the enrichment of moral thought in an increasingly complex and changing society.